Menurunkan gejala kecemasan pada gangguan kecemasan umum dengan cognitive therapy - Resti Rahmawati (Universitas Muhammadiyah Malang, 2022)
Anxiety disorder is a condition characterized by excessive and uncontrollable anxiety, fear, and worry in everyday life for no apparent reason. People with anxiety disorders usually tend to always have bad thoughts or distorted thought patterns, for example feeling that something bad will happen to them and can't stop at work and other important aspects so that their daily life is dominated by worry and fear. This subject has a distorted thinking that causes him to experience anxiety disorders. The assesment method was clinical interviews, observation, BAUM and DAP tests, self-reports and the Beck’s Anxiety Inventory. Cognitive therapy used to reduce anxiety levels.